Financing of «green» projects in the period of crisis (Journal of Economic Research & Business Administration, 2016)
In present-day society differently understands the expression «green» economy. Some believe that this new economic sector, which will improve the nature of the country. Others understand this expression as a new technology, a kind of ecosystem that are designed to help and benefit nature. Still others believe that this transition to a new stage of development, which aims to create environmentally friendly products. All of these approaches to the definition of the concept is very close to the value of the expression. «Green» economy – it’s the economy, aimed at preserving the well-being of society through the effective use of natural resources as well as ensuring the return of end-use products in the production cycle. First of all, the «green» economy is directed to the economical consumption of those resources, which are currently subject to depletion (natural resources – oil, gas) and the rational use of inexhaustible resources.At the heart of the green economy – friendly or «green» technologies. According to experts, the development of «green» economy will avoid our country ecological crisis, which has affected its scale for many post-industrial countries.
Keywords: crisis; «green» project finansirovanie; «green» ekonomika; new sectors of the economy; natural resources.